2022
DOI: 10.1186/s12920-022-01354-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel homozygous mutation in TRAPPC9 gene causing autosomal recessive non-syndromic intellectual disability

Abstract: Background The etiology of intellectual disabilities is diverse and includes both genetic and environmental factors. The genetic causes of intellectual disabilities range from chromosomal aberrations to single gene disorders. The TRAPPC9 gene has been reported to cause autosomal recessive forms of intellectual disabilities in 56 patients from consanguineous and non-consanguineous families around the world. Methods We analyzed two siblings with inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…In this study, we demonstrate by using MRI that the microcephaly of Trappc9 KO mice has a postnatal onset and is clearly established at weaning age. These findings are in line with TRAPPC9 patient data, which show microcephaly within the first year of life (Amin et al, 2022; Aslanger et al, 2022; Ben Ayed et al, 2021; Bolat et al, 2022; Hnoonual et al, 2019; Koifman et al, 2010; Penon-Portmann et al, 2023; Radenkovic et al, 2022) as well as data from other recently published Trappc9 KO mouse studies, which reported differences at postnatal days 7, 15 and 20, but not at birth (Hu et al, 2023; Ke et al, 2020). Monogenic disorders causing postnatal-onset microcephaly are less common than those causing primary microcephaly, which are mostly due to cell proliferation defects during embryogenesis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, we demonstrate by using MRI that the microcephaly of Trappc9 KO mice has a postnatal onset and is clearly established at weaning age. These findings are in line with TRAPPC9 patient data, which show microcephaly within the first year of life (Amin et al, 2022; Aslanger et al, 2022; Ben Ayed et al, 2021; Bolat et al, 2022; Hnoonual et al, 2019; Koifman et al, 2010; Penon-Portmann et al, 2023; Radenkovic et al, 2022) as well as data from other recently published Trappc9 KO mouse studies, which reported differences at postnatal days 7, 15 and 20, but not at birth (Hu et al, 2023; Ke et al, 2020). Monogenic disorders causing postnatal-onset microcephaly are less common than those causing primary microcephaly, which are mostly due to cell proliferation defects during embryogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…One of the most consistent symptoms of patients with TRAPPC9 mutations is microcephaly, which has been detected in children as early as one year of age and includes reduced white matter (e.g. corpus callosum), cerebral and cerebellar atrophies (Amin et al, 2022; Aslanger et al, 2022; Ben Ayed et al, 2021; Bolat et al, 2022; Hnoonual et al, 2019; Koifman et al, 2010; Penon-Portmann et al, 2023; Radenkovic et al, 2022). To investigate microcephaly in homozygous Trappc9 mutant mice, we determined brain volumes via MRI as well as tissue weights at birth, weaning and adult stages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human subject studies have suggested trappc9 to be a risk factor for obesity and NAFLD (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), but the relevant mechanism is not clear. In this study, we found that the deficiency of trappc9 resulted in the disruption of circulating glucose homeostasis, which was associated with hyperinsulinemia, hyperleptinemia, hyperprolactinemia, dyslipidemia, and reprogramming of glucose metabolism in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function mutations of the gene coding for the trafficking protein particle (TRAPP) complex subunit 9 (trappc9) cause an autosomal recessive syndrome with intellectual disability and malformations of various brain structures; over half of the cases exhibit obesity (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Genome-wide analyses detect differential methylation of the trappc9 gene in children with severe obesity as well as in women with a high body-mass index (12)(13)(14) and link trappc9 to non-alcoholic fatty liver disease (NAFLD) (15), the most common liver disease frequently associated with obesity (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%